School Holiday Food Provision in the UK: A Qualitative Investigation of Needs, Benefits, and Potential for Development - Graham, Pamela Louise; Crilley, Eilish; Stretesky, Paul B.; Long, Michael A.; Palmer, Katie Jane; Steinbock, Eileen; Defeyter, Margaret Anne (Frontiers in Public Health, 2016)
Access to an adequate supply of nutritious food has been recognized as a basic human right. However, many families across the UK face food insecurity, which is thought to be exacerbated during school holidays. To address this issue, some schools and community groups have chosen to roll out holiday clubs, though research into the effectiveness of such interventions is limited and no studies to date have evaluated holiday clubs being organized through schools. In an effort to address some of the limitations in the research literature, the current qualitative investigation utilized semi-structured interviews with staff involved in holiday clubs in school and community venues with the aim of gauging their views on the need for and benefits of holiday food provision in addition to potential areas for development. The investigation revealed that staff perceived many families to be facing food insecurity and isolation during the school holidays, which may be alleviated through holiday club provision. Holiday clubs were viewed as a valuable source of support for children and adults, providing food, activities and learning experiences. Staff were keen to see them implemented on a wider scale in future but suggested some areas that require attention in any future development of such provision. Findings are discussed in relation to current research, policy and practice surrounding the health and wellbeing of children and families.